The Effect of Hemoglobin Concentration on Hyperbaric Oxygen and Non-hyperbaric Oxygen in the Treatment of Hypertensive Intracerebral Hemorrhage After Operation at the High Altitude - Wei, Linjie; Lin, Chi; Xue, Xingsen; Jila, Shiju; Dai, Yalan; Pan, Li; Wei, Wei; Dun, Guodong; Shen, Yong; Zong, Taoxi; Wu, Jingjing; Li, Yafang; et al. (Frontiers in Human Neuroscience, 2022)
Background: The prognosis of hypertensive intracerebral hemorrhage (HICH) is poor at high altitudes. The objective of this study was to explore whether hyperbaric oxygen (HBO) can improve the results of computed tomography perfusion (CTP) imaging and the neurological function of patients with HICH, and effect of hemoglobin concentration on therapeutic effect. Method: The patients with HICH were treated with puncture and drainage. Some patients were treated with HBO after the operation, and the other patients received conventional treatment. CTP was detected twice, and all indices were measured. Scatter plots were used to determine the effect of hemoglobin concentration on CTP imaging. Receiver operating characteristic (ROC) curves were plotted to analyze the effects of hemoglobin concentration and hematoma volume on recovery results. The patients were followed up for 6 months. Results: Forty-one patients with HICH were treated with puncture and drainage. In total, 21 were treated with HBO after the operation, and 20 received conventional treatment as the control group. No significant differences in the CBV and CBF values of the two groups were noted before treatment. After 10 days, the values of CBV and CBF in the HBO group were significantly higher than those in the control group. A scatter diagram showed there was no significant in the HBO group, but significant correlation for the CBV and CBF values of the hematoma center, margin in the control group. The ROC curves showed that and hematoma volume had a influence on prognosis of the control group. The Glasgow Coma Scale (GOS) scores of the HBO group were significantly higher than those of the control group (p<0.05). Conclusions: HBO therapy can improve the postoperative CBV and CBF values of patients with HICH and ameliorate their prognoses. There was no significant correlation between HBO group and hemoglobin concentration on admission.